2011
DOI: 10.1161/strokeaha.110.606442
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Analysis of Robot-Assisted Therapy for Long-Term Upper-Limb Impairment After Stroke

Abstract: Background and Purpose Stroke is a leading cause of disability. Rehabilitation robotics have been developed to aid in recovery after a stroke. This study determined the additional cost of robot-assisted therapy and tested its cost-effectiveness. Methods We estimated the intervention costs and tracked participants' healthcare costs. We collected quality of life using the Stroke Impact Scale and the Health Utilities Index. We analyzed the cost data at 36 weeks postrandomization using multivariate regression mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(97 citation statements)
references
References 10 publications
1
86
0
3
Order By: Relevance
“…[110][111][112][113] However, because of the lack of high-quality evidence, both clinical and costeffectiveness, the benefits and risks of robotic, virtual reality, and gaming-based rehabilitation compared with conventional therapies remain unclear. [112][113][114][115] Large, welldesigned, multicenter studies evaluating the benefits and risks of robotic, virtual reality, and gaming therapy are clearly needed. Research that provides information on optimal dose, appropriate time to initiate such therapies, and criteria for identifying patients who will benefit most from such therapies is especially needed.…”
Section: Telerehabilitation Via Robotic Virtual Reality and Gaming-mentioning
confidence: 99%
“…[110][111][112][113] However, because of the lack of high-quality evidence, both clinical and costeffectiveness, the benefits and risks of robotic, virtual reality, and gaming-based rehabilitation compared with conventional therapies remain unclear. [112][113][114][115] Large, welldesigned, multicenter studies evaluating the benefits and risks of robotic, virtual reality, and gaming therapy are clearly needed. Research that provides information on optimal dose, appropriate time to initiate such therapies, and criteria for identifying patients who will benefit most from such therapies is especially needed.…”
Section: Telerehabilitation Via Robotic Virtual Reality and Gaming-mentioning
confidence: 99%
“…Users tend to make cost comparison between traditional therapy and any new technology for rehabilitation (like robotic rehabilitation), although there was no statistical significant difference between robotic rehabilitation cost and the usual care cost as reported by Wagner et al [30], where they compared the cost of delivering rehabilitation for three groups, first group received robotic rehabilitation, second group received use care and the third group received usual care plus intensive comparison therapy. Moreover, the clinical benefit or the effectiveness of devices is a complementary part to the cost-effectiveness trade-off, previous study by Demain et al [31] reported that the strength of clinical effectiveness as an important factor that impeded the translation of rehabilitation research into clinical practice and stressed on the urgent need for evidence from clinical settings to support assistive technology use in stroke upper-limb rehabilitation.…”
Section: Theme 1: "They Exist But…"mentioning
confidence: 98%
“…A 2011 study 9 of the MIT-Manus showed that a 36-week course of robot-assisted therapy cost several thousand dollars less than the same duration of conventional therapy, even when the cost of the devices was taken into account.…”
Section: Spring Into Actionmentioning
confidence: 99%